An Analysis of Agri-Ventures under Agri-Clinics and Agri-Business Centres (AC&ABC) Scheme in Uttar Pradesh State of India - Maheshwari, K. Sai; Mohammed, Hafis; Phand, Shahaji; Patra, Priyanka (Journal of Agricultural Extension Management, 2022)
The agriculture sector in India plays a pivotal role in the country economy through its substantial contribution to the country GDP. Agriculture and its allied sectors were the key sources of livelihood for around 70% of the population in India. Sustainability in agriculture could be achieved through Agripreneurship. Value-added agriculture and market-oriented farming through proper strategy and planning could ensure self-reliance and self-sufficiency. It could provide more employment, income, profit, food security and enable reverse migration from urban to rural by facilitating employment opportunities and empowering the rural economy. Agri-Clinics and Agri-Business Centres (AC&ABC) Scheme was introduced in 2002 by the Ministry of Agriculture and Farmers’ Welfare in association with NABARD, aiming to promote the establishment of Agri clinics and agri business centers across India. The study objective is to know about the diversity of agriventures established in Uttar Pradesh state and its impact. It also analyzes the challenges faced by agripreneurs and measures taken to overcome them. A total of 130 samples was collected among candidates who established ventures spread across Uttar Pradesh state. Rank Based Quotient had been conducted to know the constraints faced by agripreneurs. Result follows that representation of vulnerable sections was low. Furthermore, constraints concerning finance and a lack of entrepreneurial knowledge and skills were observed. Meanwhile, the scheme had helped generate employment, cover more farmers, and double the income of agripreneurs.